2022
DOI: 10.1038/s42003-022-03877-w
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine’s cerebrovascular vasoconstriction is associated with astrocytic Ca2+ increase in mice

Abstract: Human and animal studies have reported widespread reductions in cerebral blood flow associated with chronic cocaine exposures. However, the molecular and cellular mechanisms underlying cerebral blood flow reductions are not well understood. Here, by combining a multimodal imaging platform with a genetically encoded calcium indicator, we simultaneously measured the effects of acute cocaine on neuronal and astrocytic activity, tissue oxygenation, hemodynamics and vascular diameter changes in the mouse cerebral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
1
8
1
Order By: Relevance
“…Analysis of temporal correlations showed that cocaine-induced Ca 2+ A increases had strong negative correlations with the CBFv decreases. These ndings are in agreement with our recent results obtained in separate groups of animals 35 . In that study we used single virus containing GCaMP6f (not jRGECO1a) delivered into the somatosensory cortex and reported that cocaine-induced neuronal Ca 2+ N increases recovered by 30min followed by a downshoot similar to our observations in this study but in the PFC (Fig.…”
Section: Ca 2+supporting
confidence: 94%
See 3 more Smart Citations
“…Analysis of temporal correlations showed that cocaine-induced Ca 2+ A increases had strong negative correlations with the CBFv decreases. These ndings are in agreement with our recent results obtained in separate groups of animals 35 . In that study we used single virus containing GCaMP6f (not jRGECO1a) delivered into the somatosensory cortex and reported that cocaine-induced neuronal Ca 2+ N increases recovered by 30min followed by a downshoot similar to our observations in this study but in the PFC (Fig.…”
Section: Ca 2+supporting
confidence: 94%
“…It also allowed us to control for group variability. For example, in our prior study using separate groups of mice, the amplitude of cocaineinduced Ca 2+ A was 3 fold lower than that of the Ca 2+ N response 35 , whereas in the current study that measured them in the same animals there were no differences between the peak values of Ca 2+ A and Ca 2+ N (i.e., 2.97±0.42% vs 2.46±0.42%, p=0.82). This discrepancy likely re ects differences between the groups (i.e., WT vs GFAP-cre mice) in our prior study.…”
Section: Ca 2+contrasting
confidence: 82%
See 2 more Smart Citations
“…The mice in the cocaine abuse/use model showed elevated BP and aortic stiffness 30 . Cocaine abuse has been shown to induce vasoconstriction [43][44][45][46][47] . Ca 2+ plays a central role in excitation-contraction coupling in vascular SMCs among other functions (reviewed in 48 ).…”
Section: Cocaine and CM Treatment Increase Intracellular Free Calcium...mentioning
confidence: 99%